Kajian Konseptual Kontribusi Gaya Belajar Terhadap Perilaku Belajar - Moh. Sutomo (Program Studi PGMI, IAI Al-Falah As-Sunniyyah Kencong, 2019)
Studies on learning styles are always interesting to study, even many studies have emerged, but how the behavioral orientation of each learning style is not so popular to study. That teachers as students need to understand the learning style of learners is indeed a necessity, but how the orientation of learners' behavior with the learning styles they have then is used as feedback for students to evaluate the learning services provided have not been so much described in scientific studies. This paper aims to describe various learning styles and their consequences in the form of learning behavior orientation of the learner, so that the end learners understand how to provide services that satisfy the learning (learners) so that effective and efficient achievement of learning outcomes can be achieved.Keywords: learning style, learning behavior.